Exploring the Affordances of Place-Based Education for Advancing Sustainability Education: The Role of Cognitive, Socio-Emotional and Behavioural Learning - Felicity Hernandez Gonzalez (Education Sciences, 2023)
The present paper explores the affordances of place-based education (PBE) to enhance the goals of sustainability education (SE). UNESCO, the leading international body responsible for advancing SE, assigns a central role to the three dimensions of cognitive, socio-emotional and behavioural learning as a means for advancing sustainability and the seventeen Sustainable Development Goals. Thus far, little research attention has been given to examining pedagogical approaches that may be effective in supporting these learning dimensions. PBE has risen over the past years as a holistic educational approach that may be well situated for supporting SE goals. To evaluate its affordances, the study put forward the objectives to (i) examine the application of cognitive, socio-emotional and behavioural learning dimensions in empirical studies employing PBE; and (ii) examine the overall contribution of PBE to developing students’ sustainability awareness, as reflected in the PBE case-study literature. Multiple case-study analysis was employed for examining secondary resources, comprised of four PBE case studies reported in the literature. It was found that the implementation of PBE in the context of SE produced holistic learning outcomes across the three dimensions, as early as in kindergarten students. Through direct content with nature and the local community, students’ agency, voice and action competence increased, having ripple effects across the community, connecting the local with the global. PBE advanced inter-cultural sensitivity and promoted the inclusion of Indigenous knowledge in SE.